Antimicrobial peptides in the innate immune system of the lung - Hiemstra, Pieter S. (Henry Stewart Talks, 2014)
Antimicrobial peptides (AMPs) are evolutionary conserved elements of the innate immune system, AMPs are active against a broad spectrum of pathogens, including multidrug resistant bacteria, Epithelial expression of AMPs is tightly regulated, Regulation of epithelial vitamin D metabolism affects expression of AMPs, AMPs act in a complex working environment, which is markedly altered by disease activity